Analysis of the Effectiveness of the Performance of the Government's Internal Supervisory Apparatus in the Field of Performance and Financial Supervision at the Inspectorate Mandailing Natal Regency - Prima, Andi; Ritonga, Syafruddin; Jamaluddin, Yanhar (Journal of Public Representative and Society Provision, 2025)
This research is motivated by the need for adequate supervision to improve the efficiency and effectiveness of local government implementation, especially in government and development tasks. This study aims to analyze the effectiveness of the performance of the Government Internal Supervisory Apparatus (APIP) in the field of performance and financial supervision at the Regional Inspectorate of Mandailing Natal Regency, and identify factors that hinder the effectiveness of this performance. This study uses Sarwoto's (2010) theory as the basis for analysis. The results showed that accuracy is an essential guideline in carrying out APIP duties. Mandailing Natal Regency Inspectorate auditors comply with established implementation standards to prevent fatal errors. Timeliness is a key element in collecting and evaluating activities to accelerate improvements. A centralized supervision system is implemented by laws and regulations to overcome problems in vulnerable areas. In addition, performance effectiveness is also assessed from the conformity between economic and organizational aspects, where detected standard deviations can help determine the necessary corrective actions. This study concludes that the effectiveness of APIP performance is influenced by adherence to standards, timeliness, and the application of a centralized system, which contribute to achieving regional supervision objectives.